Discrepancies between cortical and behavioural long‐term readouts of hyperalgesia in awake freely moving rats. (5th May 2016) - Ljungquist, B.; Jensen, T.; Etemadi, L.; Thelin, J.; Lind, G.; Garwicz, M.; Petersson, P.; Tsanakalis, F.; Schouenborg, J.
Abstract: Background: It is still unclear to what extent the most common animal models of pain and analgesia, based on indirect measures such as nocifensive behaviours, provide valid measures of pain perception. Methods: To address this issue, we developed a novel animal model comprising a more direct readout via chronically (>1 month) implanted multichannel electrodes (MCE) in rat primary somatosensory cortex (S1; known to be involved in pain perception in humans) and compared this readout to commonly used behavioural pain‐related measures during development of hyperalgesia. A translational method to induce hyperalgesia, UVB irradiation of the skin, was used. Localized CO2 laser stimulation was made of twenty skin sites (20 stimulations/site/observation day) on the plantar hind paw, before and during the time period when enhanced pain perception is reported in humans after UVB irradiation. Results: We demonstrate a 2–10 fold significant enhancement of cortical activity evoked from both irradiated and adjacent skin and a time course that corresponds to previously reported enhancement of pain magnitude during development of primary and secondary hyperalgesia in humans. In contrast, withdrawal reflexes were only significantly potentiated from the irradiated skin area and this potentiation was significantly delayed as compared to activity in S1. Conclusions: The present findings provide direct evidence that chronic recordings in S1 in awake animals can offer a powerful, and much sought for, translational model of the perception of pain magnitude during hyperalgesia. What does this study add?: In a novel animal model, chronic recordings of nociceptive activity in primary somatosensory cortex (S1) in awake freely moving rats are compared to behavioural readouts during UVB‐induced hyperalgesia. Evoked activity in rat S1 replicates altered pain perception in humans during development of hyperalgesia, but withdrawal reflexes do not.